Stabilizing biogas processes at high ammonia : effects of acetate pulse-feeding on the microbial population - Dolk, Oscar (SLU/Department of Molecular Sciences, 2020)
This study investigated the problem of ammonia inhibition in biogas reactors, commonly occurring when protein rich substrates are used in anaerobic digestion processes. Ammonia inhibition is one of the foremost causes of failure in anaerobic digestion, leading to process instability, with symptoms commonly expressed as; reduction in biogas produced, decreased methane content in the gas and accumulation of volatile fatty acids. Increasing ammonia concentrations lead to a shift in the dominant pathways for methane production, from acetoclastic methanogens to syntrophic acetate-oxidizing bacteria, working with hydrogenotrophic methanogens. This shift occurs as the acetoclastic methanogens are sensitive to increasing ammonia concentrations. Both pathways utilize acetate, which apart from ammonia, is one of the factors that also is believed to regulate the level of the different pathways. The aim of this study was to evaluate the impact of subjecting anaerobic digestion processes in biogas reactors to increasing levels of ammonia and to study the performance of the reactors as well as the potential microbial changes that occur when reactors are supplemented with acetate simultaneous with the ammonia increases. The total ammonium-nitrogen was successfully increased in the reactors to concentrations known to cause ammonia inhibition towards the end of one hydraulic retention time. The increase in total ammonium-nitrogen correlated with increased H2S concentrations in the reactors and an accumulation of volatile fatty acids. Acetate addition resulted in higher acetate concentration in the reactors, but without accumulation. The acetate addition possibly caused an increase in the gene abundance of hydrogenotrophic methanogenic order Methanomicrobiales and the genus Methanoculleus. No significant change in gene abundance of acetoclastic methanogens or syntrophic acetate-oxidising bacteria occurred in response to the increase in ammonia and acetate in this study. The lack of microbial compositional changes could have been due time of the study, being too short for changes in the microbial composition to happen. Moreover, the acetate-enrichment was possibly too low to stimulate growth of syntrophic acetate-oxidising bacteria when compared to concentrations in other studies.